Product Quality, WOM, and Store Image on Consumer Purchase Decisions: Evidence from Mbarshopp Store Bali - Tjokorda Gde Agung Wijaya Kesuma Suryawan; Made Mulia Handayani; Cokorda Istri Agung Vera Nindia Putri; Ni Putu Ratih Purnama Yeni (CV. Ulil Albab Corp, 2024)
Purchasing decisions are crucial for businesses to thrive, especially given the high competition in the business world. This study investigates the influence of product quality, word of mouth, and store image on purchasing decisions at the Mbarshopp Store in Bali. Specifically, it aims to determine both the partial and simultaneous effects of these variables on purchasing decisions. A sample of 100 respondents was selected using purposive random sampling method. Data were analyzed through validity and reliability tests, classical assumption tests, multiple linear regression analysis, determination analysis, t-tests, and F-test. The findings indicate both product quality and store image individually have a positive and significant impact on purchasing decisions. Conversely, word of mouth has an insignificant effect on purchasing decisions. However, when considered together, product quality, word of mouth, and store image have a significant and positive effect on purchasing decisions. This study provides valuable insights for retailers aiming to enhance their marketing strategies and improve customer purchase decisions through focused improvements in product quality and store image. The research contributes to the field of marketing management by offering empirical evidence on the relative importance of product quality, word of mouth, and store image in influencing consumer behavior.